THE IMPORTANCE OF GREEN TARGET COSTING AND CONCURRENT ENGINEERING TECHNIQUES IN ACHIEVING SUSTAINABLE COMPETITIVE ADVANTAGES-APPLIED RESEARCH IN THE IRAQI GENERAL CEMENT COMPANY - Dr. Mohammed Sameer Dherib AL Robaaiy; Lecturer Dr. Basim Abdullah kadhim; Lecturer Dr. Raad Abidmuslim Hraiga (Scholars Digest Publishing, 2024)
The research aims at the importance of the Concurrent engineering techniques and the green target cost in providing an environmentally friendly product, because these two technologies are among the most important tools that emerged as a result of following business strategies that change rapidly with market requirements and the essence of the advanced production process, by manufacturing products that meet the desires of customers in the shortest possible time and lowest costs. To this end, the Babylon laboratory was chosen. The research reached several conclusions represented in the shift from product development from succession to synchronization, which enables it to respond quickly by reducing the time required for products to enter the market and adapting to changing work environments. Following the two techniques of concurrent engineering and green target cost in product development is a shortcut to the product design and development process. The most important recommendations are directing modern technologies to serve the environment due to the trend of global interest in the environment due to environmental pollution and the lack of natural resources, especially scarce resources.
Keywords: Concurrent Engineering, Green Target Cost, Sustainable Competitive Advantage.